Expediente - Villela, Adauto (Rónai – Revista de Estudos Clássicos e Tradutórios, 2015)
Rónai – Revista de Estudos Clássicos e Tradutórios Volume 3, Número 1 Editores: Prof. Dr. Adauto Lúcio Caetano Villela Profa. Dra. Fernanda Cunha Sousa Conselho Editorial: Adauto Lúcio Caetano Villela - UFJF Alexandre Prudente Piccolo – USP Bernardo Guadalupe dos Santos Lins Brandão – UFPR Brunno V. G. Vieira – UNESP/Araraquara Carlos Renato Rosário de Jesus – UEA (convidado adhoc) Charlene Martins Miotti – UFJF Fernanda Cunha Sousa – UFJF Giovana Cordeiro Campos de Mello – UFF Leni Ribeiro Leite – UFES Luís Carlos Lima Carpinetti – UFJF Matheus Trevizam – UFMG Neiva Ferreira Pinto – UFJF Paula Godói Arbex – UFU Raquel Fellet Lawall – UFJF (convidada adhoc) Roberto Carlos Assis - UFPB Sandra Aparecida Faria de Almeida – UFJF Silvina Carrizo – UFJF (convidada adhoc) Tatiana Oliveira Ribeiro – UFRJ Assistente editorial: Luana Campos Leal Rodrigues Capa: Iago Medeiros Campus Universitário Martelos Rua José Lourenço Kelmer, s/n. Bairro São Pedro CEP: 36036-900 – Juiz de Fora – MG